Bridging Theory to Practice: Assessing EFL Preservice Teachers' Competence in Designing Readability-Focused PDP Lesson Plans - Putri, Nanda Dewita; Sari, Afifah Linda (Proceeding International Conference on Education, 2025)
This qualitative study investigates the proficiency of English Language Education (EFL) preservice teachers in developing readability-enhanced lesson plans within the Pre-During-Post (PDP) framework. While effective lesson planning is crucial for quality instruction and reading comprehension, students often struggle to translate theoretical pedagogical principles into practical, cohesive lesson designs. Employing content analysis of 68 lesson plans and in-depth interviews with 21 fourth-semester students from Antasari State Islamic University, the research revealed that students grasped the procedural aspects of the PDP framework but faced significant challenges in applying its conceptual elements, particularly in the pre- and during-reading stages. Key difficulties included distinguishing between task types, aligning activities with learner proficiency and objectives, and over-reliance on instructor guidance or AI tools. Furthermore, readability issues limited content clarity, resulting in inconsistent formatting and imprecise PDP terminology. The study highlights a substantial theory-practice divide in lesson plan design, advocating for focused training, practical demonstrations, and structured feedback within teacher education programs. This research provides valuable insights for curriculum designers and educators seeking to enhance students' pedagogical competence in creating effective, learner-centered reading lessons.